The Implementing SOSTAC Model for Marketing Communication Strategy: A Case Study of Assalam Hypermarket - Aditya, Muhammad Hanif; Muanas, Arif; Khaldun, Muhammad Ibnu (UIN Raden Mas Said Surakarta, 2024)
This study aims to analyse the implementation of marketing communication strategies using the SOSTAC (Situation, Objectives, Strategy, Tactics, Action, Control) framework at Assalam Hypermarket, Sukoharjo. The research method used is a qualitative descriptive approach, which consists of three stages: Pre-Field, Field Implementation, and Data Analysis. Data collection was conducted through in-depth interviews with the CEO and the Marketing and Public Relations Division of Assalam Hypermarket, observation, and documentation. Integrated Marketing Communication (IMC) approaches consistently, from branding to integrated advertising and event marketing. The findings reflect the company's commitment to building engagement with customers and communities, and show that Assalam Hypermarket not only focuses on implementing marketing strategies, but also actively monitors and evaluates their effectiveness. This research is expected to provide valuable insights for the development of marketing communication strategies in the Islamic retail sector in Indonesia